24-hour ambulatory blood pressure measurement using a novel non-invasive, cuff-less, wireless device. (14th October 2021) - Nachman, D; Gilan, A; Goldstein, N; Constantini, K; Littman, R; Eisenkrafta, A; Grossmanc, E; Gepnerc, Y
Abstract: Background: Ambulatory blood pressure monitoring (ABPM) using cuff-based devices is used for diagnosis and treatment of hypertension. Technical limitations, low compliance and complex procedures limit their use. Purpose: The aim of the present study was to test the accuracy of a new technique of 24H ABPM using a photoplethysmography (PPG)-based, wearable device (Wrist-monitor) as compared to the standard cuff-based ABPM device. Methods: In this prospective observational study, 24H ABPM was performed in parallel for both devices on volunteers aged 18–65 years, while documenting their daily activities. Level of comfort and activity disturbance of both devices were recorded. Linear regression and Bland-Altman were used to evaluate the agreement between devices. Receiver Operating Characteristic (ROC) curve analysis was used to assess the capability of the Wrist-monitor to identify abnormal BP values. Results: The study included 28 subjects (18 men) mean age 41.5±16.2 years. Bland-Altman analysis resulted in 24H bias of −1.1 mmHg for both diastolic blood pressure (DBP) and systolic blood pressure (SBP). Mean daytime bias was −1.9 mmHg for DBP and SBP, while nighttime bias was smaller (0.7 and 0.4 mmHg for DBP and SBP respectively). ROC curve analysis on all BP readings (n=2381) yielded a mean area under the curve (AUC) for 24H of 0.965 for both SBP and DBP. 24H ABPM with the Wrist-monitor caused significantly less inconvenience compared to the cuff-based device (p<0.001). Conclusions: The cuff-less device provides comparable measurements to those obtained with the currently used cuff-based ABPM device, with significantly less inconvenience to the subject. FUNDunding Acknowledgement: Type of funding sources: Private company. Main funding source(s): The ABPM devices were given for free by BioBeat LTD. Petach-Tikva, Israel. No other support was given.